2013
DOI: 10.1007/s13762-013-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological and chemical analyses of a laboratory-scale biofilter for oxygenate bioremediation in simulated groundwater

Abstract: Microbial remediation of methyl tert-butyl ether-contaminated aquifers has been widely studied since their cost/efficiency ratios are lower than other remediating techniques. Based on previous studies, simultaneous assessment of two inocula (Acinetobacter calcoaceticus M10 and a co-culture between strain M10 and Rhodococcus ruber E10) was performed for methyl tert-butyl ether bioremediation in a designed pilot-scale biofilter. A noninoculated biofilter was included for comparison. Temporary bioremediation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among the existing chemical compounds in use fuels of most countries could be noted to MTBE (Zhang et al 2019). Despite the bans in some countries, it has become the second most common organics detected contamination in municipal groundwaters (Levchuk et al 2014, Purswani et al 2014, Abbasi et al 2020). The American environmental protection agency has been representing the recommended allowable limit of 20 to 40 µg/L for drinking water on the basis of threshold limits of smell and taste and has been placed this substance among compounds that is probable carcinogen for humans (Hu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing chemical compounds in use fuels of most countries could be noted to MTBE (Zhang et al 2019). Despite the bans in some countries, it has become the second most common organics detected contamination in municipal groundwaters (Levchuk et al 2014, Purswani et al 2014, Abbasi et al 2020). The American environmental protection agency has been representing the recommended allowable limit of 20 to 40 µg/L for drinking water on the basis of threshold limits of smell and taste and has been placed this substance among compounds that is probable carcinogen for humans (Hu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Basic and applied research on MTBE biodegradation has increased in order to develop new technologies to treat contaminated ecosystems such as membrane bioreactor treating 5 mg l −1 MTBE in mixed liquor, upflow fixed‐bed reactors or an aerated submerged biofilter treating 100 mg l −1 of spiked groundwater to observe microbial events in recent groundwater spills . Among ex‐situ practices for MTBE‐contaminated groundwater bioremediation, those based on the use of fixed biofilms have gained great prominence, since protection provided by the biofilm matrix allows for higher cell survival following adaptation to confer an increased production rate or enabling the acquisition of specific enzymes for toxic compound degradation . However, the results offered by these studies revealed significant losses of oxygenate by air‐stripping as well as slow growth and poor biomass yield of MTBE degraders, especially when a pure culture was used as the bioreactor inoculum.…”
Section: Introductionmentioning
confidence: 99%
“…DD8, R. ruber EE6, Agrobacterium sp. MS2, and Paenibacillus etheri SH7 T (Guisado et al, 2013 , 2015 , 2016 ; Purswani et al, 2014 ). The function, observed in our HT-Growth method as growth yield and rate in different xenobiotic compounds, will help determine which bacterial consortium is suitable as an inoculum for a biofilm-based remediating reactor.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilms form in the interfaces of different density states, and have been found in “extreme” environments such as glacier-fed streams (Wilhelm et al, 2013 ) or near hydrothermal vents (Hall-Stoodley et al, 2004 ). Their resistance to external changes make biofilms the potentially leading bacterial-state for bioremediation (Fortin and Deshusses, 1999 ; Kharoune et al, 2001 ; Purswani et al, 2014 ). One of the most important decisions when selecting a microbial inoculum is whether to use an existing mixed-microbial population (e.g., sludge from a prior existing bioreactor) or select pure microbial cultures.…”
Section: Introductionmentioning
confidence: 99%